The centrality of the Right to care in the Covid-19 crisis in Latin América. Opportunities at risk - Pautassi, Laura Cecilia (2020)
The COVID-19 pandemic has brought about a change of scenery in the field of human rights that must be addressed in all its dimensions. In Latin America the pandemic erupted in a moment when States were already challenged in their regulations and response capacity to COVID-19. The recent measures adopted to prevent the pandemic first and foremost prescribe the restriction of movement and mandatory preventive social isolation. This brings to light the configuration of care within households and the unfair social organization around it. Care is usually understood as any activity that is essential in satisfying the basic needs for human existence and reproduction, providing the physical and symbolic elements that allow humans to live in society. This paper analyzes the scope of the recognition of care as work but particularly as a human right, (the right to care, to be cared for and to self-care), based on the survey of theoretical and empirical studies developed in Latin America. The objective is to present the conceptual framework and empirical evidence pre-existing to the Covid 19 crisis regarding care, to identify the lack of its social distribution and the way in which it focuses on women to the detriment of their autonomy. The hypothesis guiding the analysis is that until universal, cross-cutting policies are adopted, with regular budgets and based on a gender and rights approach, efficient responses to the pandemic will not be achieved. The argument that the article introduces (set in a tour of some of the Latin American countries and the recommendations of the human rights protection bodies) is that despite the allusion to universality, the policies end up targeting due to vulnerability without promoting comprehensive actions, absolutely necessary during the crisis, but to design the way out.